2022
DOI: 10.1542/hpeds.2022-006545
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Needs of Children Hospitalized for Eating Disorders During the COVID-19 Pandemic

Abstract: BACKGROUND AND OBJECTIVES: Throughout the COVID-19 pandemic, there has been an increase in hospital admissions for adolescents with eating disorders (EDs). However, there is a paucity of information on how this increase has affected hospitalization courses and disposition planning. We sought to describe the changes in hospitalizations for EDs at our institution during the pandemic. METHODS: We reviewed charts of patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Earlier pandemic studies noted higher medical acuity in patients hospitalized with ED in the first year of the pandemic as well as increased or new self‐reported restrictive symptomatology directly attributed to the pandemic and quarantine measures (Agostino et al, 2021; Asch et al, 2021; Feldman et al, 2023; Haripersad et al, 2021; Hartman‐Munick et al, 2022; Lin et al, 2021; Otto et al, 2021; Parsons et al, 2021; Shum et al, 2022). Prolonged disruption of daily routines and constraints on out‐of‐home activities, especially cessation of athletic programs and gym restrictions, may have increased weight or body image concerns, thereby negatively impacting eating, exercise, and mental resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier pandemic studies noted higher medical acuity in patients hospitalized with ED in the first year of the pandemic as well as increased or new self‐reported restrictive symptomatology directly attributed to the pandemic and quarantine measures (Agostino et al, 2021; Asch et al, 2021; Feldman et al, 2023; Haripersad et al, 2021; Hartman‐Munick et al, 2022; Lin et al, 2021; Otto et al, 2021; Parsons et al, 2021; Shum et al, 2022). Prolonged disruption of daily routines and constraints on out‐of‐home activities, especially cessation of athletic programs and gym restrictions, may have increased weight or body image concerns, thereby negatively impacting eating, exercise, and mental resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Research through the first year of the pandemic in both pediatric and adult literature reported increased rates of ED‐related encounters across healthcare environments. Concerns for worsening medical acuity of patients, especially with restrictive or compensatory behaviors like AN and BN, have been reported using encounter rates, hospitalization rates, and/or longer duration of stay as indirect markers of medical severity (Agostino et al, 2021; Asch et al, 2021; Feldman et al, 2023; Haripersad et al, 2021; Hartman‐Munick et al, 2022; Lin et al, 2021; Otto et al, 2021; Parsons et al, 2021; Shum et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Some patients and their families linked the onset of lockdown as a trigger for hospital admission. The overall increase in hospital admissions for eating disorder exacerbations and prolonged stays has resulted in an increased demand for care related to the treatment of these disorders [ 61 , 62 , 63 ].…”
Section: Psychological Aspects Of Eating Disorders During the Covid-1...mentioning
confidence: 99%
“…Shortened length of stay (LOS) was found at pediatric hospitals in Israel and Italy ( 26 , 27 ), yet prolonged LOS was observed at a large pediatric hospital with a specialized ED-treatment program in North America and at some Departments of Child and Adolescent Psychiatry in European Countries ( 31 ). Most of the few available studies found an increase in co-occurring mental health disorders in children and youth with ED ( 28 , 32 , 33 ). German studies investigating the impact of the COVID-19 pandemic on ED, and especially AN, in children and youth are scarce, but mostly concur with international data, indicating an increase of youth hospitalized for ED during the COVID-19 pandemic ( 18 , 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%